Statárium - Sipos, András (Hungary, 1989)
Through three case studies, the documentary film explores the methods used in the kulak trials in Hungary. In the 1950s due to political pressure, wealthy farmers, the so-called kulaks, were declared class enemies, and were convicted. In these show trials, standard court hearings were avoided and statutory courts were set up. The accused were tortured to make them confess acts that they never committed , accidental fires were declared to be deliberate arson, which was classified as sabotage and treason, and the innocent farmers were condemned and hanged.
Keywords: Documentary films